KEWENANGAN AYAH BIOLOGIS SEBAGAI WALI NIKAH TERHADAP ANAK LUAR KAWIN - Tiara Oktaviani (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT This thesis concerns with analysis of authority a biological father as the marriage guardian to illegitimate children. The purpose of doing this research are to know how the status of illegitimate children and rhe authority of their biological father depend on indonesian marriage law and four big madzab.The design of this research is descriptive qualitative design. The data collected by searching literature related to legislation, policy and opinion of the experts, and by reading and studying books and documents related to this research and legislation applicable. The data also collected by interview with people related to purpose of this study. In analyzing this research. The researcher used normative law approach. In this approach, the researcher observed and analyzed applicablelegislation to moeslem’s law. The researcher also implemented the regulation to solve the problem of status illegitimate children related to the authority of their biological father. This researcher was done at pengadilan agama samarinda for five working days.